Murine Myocardial Transcriptome Analysis Reveals a Critical Role of COPS8 in the Gene Expression of Cullin-RING Ligase Substrate Receptors and Redox and Vesicle Trafficking Pathways - Abdullah, Ammara; Eyster, Kathleen M.; Bjordahl, Travis; Xiao, Peng; Zeng, Erliang; Wang, Xuejun (Frontiers in Physiology, 2017)
Background- The COP9 signalosome (CSN) consisting of 8 unique protein subunits (COPS1 through COPS8) serves as the cullin deneddylase, regulating the catalytic dynamics of cullin RING ligases (CRLs), the largest family of ubiquitin ligases. Supported primarily by the decrease of substrate receptor proteins of CRLs in cells deficient of a CSN subunit, CSN-mediated cullin deneddylation is believed to prevent autoubiquitination and self-destruction of the substrate receptor in active CRLs. However, it is unclear whether the decrease in substrate receptors is solely due to protein destabilization. Moreover, our prior studies have demonstrated that cardiac specific knockout of Cops8 (Cops8-CKO) impairs autophagosome maturation and causes massive necrosis in cardiomyocytes but the underlying mechanism remains poorly understood. Given that Cops8 is nucleus-enriched and a prior report showed its binding to the promoter of several genes and association of its ablation with decreased mRNA levels of these genes, we sought to determine the dynamic changes of myocardial transcriptome in mice with perinatal Cops8-CKO and to explore their functional implications. Methods and Results- Myocardial transcriptomes of Cops8(flox/flox), Cops8(flox/+)::Myh6-Cre, and Cops8(flox/flox)::Myh6-Cre littermate mice at postnatal 2 and 3 weeks were analyzed. The data were imported into an in-house analysis pipeline using Bioconductor for quantile normalization and statistical analysis. Differentially expressed genes (DEGs) between groups at each time point or between time points within the group were revealed by t-test. Genes with p<0.05 after Benjamini and Hochberg false discovery rate correction for multiple hypothesis testing were considered as significant DEGs. We found that (1) the Ingenuity Pathway Analysis revealed significant enrichment of DEGs in multiple pathways, especially those responding to oxidative stress, in homozygous Cops8-CKO hearts at both 2 weeks and 3 weeks, corroborating the occurrence of massive cardiomyocyte necrosis at 3 weeks; (2) the decreases in multiple CRL substrate receptor proteins were associated with decreased transcript levels; and (3) enrichment of DEGs in the chromatin remodeling pathway and the microtubule motility and vesicle trafficking pathways. Conclusions- Our data are consistent with a notion that Cops8/CSN plays a role in the transcriptional regulation of CRL substrate receptors and in the redox and vesicle trafficking pathways.